Impact of mastectomy for breast cancer on spinal curvature: Considerations when treating patients with scoliosis. Issue 10 (25th August 2020) - Gutkin, Paulina M.; Kapp, Daniel S.; von Eyben, Rie; Dirbas, Frederick M.; Horst, Kathleen C.
Abstract: Objective: Mastectomy has been shown to influence body posture in women; however, there are limited data outlining changes in spine curvature after mastectomy in patients with scoliosis. We sought to quantify changes in spine curvature after mastectomy for breast cancer. Methods: We conducted a retrospective review of 62 patients with scoliosis who underwent mastectomy for breast cancer at a single institution between 1995 and 2018. Preoperative and postoperative radiographs were used to measure Cobb angles to assess lateral spinal curvature. Changes in Cobb angle were compared using paired two‐tailed t‐tests. The relationship between mass of breast removed and changes in Cobb angle was modeled using a linear regression. Results: The median follow‐up after mastectomy was 7.9 years (range 0.9‐21.5). Median age was 62 years (range 30‐85). Of 62 patients, 10 (16%) expressed that their back pain became worse after mastectomy. Nineteen patients had evaluable radiographs before and after mastectomy. In these patients, the average change in Cobb angle was 4.7° (range −0.2‐12.2). Cobb angle significantly increased after mastectomy ( P  < .0001). Although not statistically significant, average Cobb angle was greater for patients who underwent unilateral compared to bilateral mastectomy ( P  = .09). Mass of breast removed significantly correlated with the difference in Cobb angle for patients who underwent unilateral mastectomy ( P  = .0006), but not for bilateral mastectomy ( P  = .55). Conclusions: In this understudied patient population, mastectomy significantly increased the change in spine curvature. Further care should be taken to assess patient‐reported pain and quality of life in patients with spine morbidity who undergo mastectomy for breast cancer.